Ensino de astrobiologia a partir da biosfera terrestre em comparação com a composição química dos principais satélites naturais de Júpiter - Rosa, Marcia Nogueira Melo da (2022)
The present work discusses how Astrobiology, an area of ​​study that combines knowledge of Biology with that of Astronomy, can serve as a transversal theme in the discipline of Science in Elementary School. The insertion of Astrobiology in Basic Education is a proposal that seeks to awaken in the teacher the role of mediator of knowledge through scientific investigation. Thus, the objective of this investigation was to demonstrate that it is possible to teach Astrobiology, based on terrestrial abiotic factors in comparison with the main satellites of Jupiter. The research work was designed to be applied in the 6th year of Elementary School of Basic Education. During the study, it was noticed that the lines of research in Astrobiology could be conveyed within the thematic units recommended by the BNCC. In this way approaching Astrobiology in Science classes is to make teaching more dynamic and attractive because it is a field of research that arouses interest and imagination. The educational products linked to this study were the production of a Didactic Sequence and a Pop-Up Book. Due to the Covid-19 pandemic, educational products were not applied in the school unit. It is hoped that this study will serve as a basis and motivation for teachers to add Astrobiology to their pedagogical planning. It is necessary a greater diffusion of Astrobiology in school units, as it is a science that offers eleven thematic areas that can be implemented in an interdisciplinary way.